ISOTOPIC-GEOCHEMICAL CHARACTERISTICS OF THE LOST CITY HYDROTHERMAL FIELD - Dubinina E.O.; Chernyshev I.V.; Bortnikov N.S.; Gol'tsman Yu.V.; Bairova E.D.; Mokhov A.V.; Lein A.Yu.; Sagalevich A.M. (My University, 2007)
The isotopic (δD, δ18O, δ13C, and 87Sr/86Sr) and geochemical characteristics of hydrothermal solutions from the Mid-Atlantic Ridge and the material of brucite-carbonate chimneys at the Lost City hydrothermal field at 30°N, MAR, were examined to assay the role of the major factors controlling the genesis of the fluid and hydrothermal chimneys of the Lost City field. The values of δD and δ18O in fluid samples indicates that solutions at the Lost City field were produced during the serpentinization of basement ultramafic rocks at temperatures higher than 200°C and at relatively low fluid/rock ratios (<1). The active role of serpentinization processes in the genesis of the Lost City fluid also follows from the results of the electron-microscopic studying of the material of hydrothermal chimneys at this field. The isotopic (δ18O, δ13C, and 87Sr/86Sr) and geochemical (Sr/Ca and REE) signatures indicate that, before its submarine discharging at the Lost City field, the fluid filtered through already cold altered outer zones of the Atlantis Massif and cooled via conductive heat loss. During this stage, the fluid could partly dissolve previously deposited carbonates in veins cutting serpentinite at the upper levels of the Atlantis Massif and the carbonate cement of sedimentary breccias underlying the hydrothermal chimneys. Because of this, the age of modern hydrothermal activity at the Lost City field can be much younger than 25 ka.